Economic evaluation of hepatocellular carcinoma surveillance in chronic hepatitis B patients with virological remission - Fang, Kailu; Li, Shuwen; Lin, Yushi; Zhang, Yu; Wu, Jie (BMC public health, 2024)
Subsequent risk of hepatocellular carcinoma (HCC) persists in chronic hepatitis B (CHB) patients with virological remission. We aimed to assess the cost-effectiveness of HCC surveillance in those patients and determine appropriate age to commence or discontinue surveillance. We developed an individual-based state transition model, simulating the advancement of HCC in CHB patients with virological remission. We used this model to compare the incremental cost-effectiveness ratio (ICER) and long-term health outcomes of biannual or annual HCC surveillance for varying durations with no surveillance. For compensated cirrhosis patients with CHB, biannual surveillance was not cost-effective for all age groups, while annual surveillance was cost-effective for patients aged 55 to 70 (ICER USD 28,076 / quality-adjusted life years [QALY] gained), which detected 176 additional early HCC cases in a 100,000-person cohort compared to no surveillance. In CHB patients with advanced fibrosis, annual surveillance for patients aged 40 to 75 was the most cost-effective strategy (ICER USD 4,984/QALY gained), which detected 289 additional early HCC per 100,000 patients. Annual surveillance for patients with compensated cirrhosis or advanced fibrosis was a more cost-effective option that demonstrated substantial economic benefits, being slightly less effective than biannual surveillance at a significantly lower cost, providing insights for professionals in evaluating HCC surveillance among high-risk patients in China.